Rod-like β-FeOOH@poly(dopamine)–Au–poly(dopamine) nanocatalysts with improved recyclable activities. Issue 20 (28th May 2015) - Mao, Ya; Jiang, Wanquan; Xuan, Shouhu; Fang, Qunling; Leung, Ken Cham-Fai; Ong, Beng S.; Wang, Sheng; Gong, Xinglong
<x xml:space="preserve">Abstract</x> A novel rod-like β-FeOOH@poly(dopamine)–Au–poly(dopamine) core–shell nanocomposite with significantly improved recyclability is developed for catalysis.